Marine biodiversity discovery: the metrics of new species descriptions - Bouchet, Philippe; Decock, Wim; Lonneville, Britt; Vanhoorne, Bart; Vandepitte, Leen (Frontiers in Marine Science, 2023)
Based on the World Register of Marine Species (WoRMS), there are currently c. 242,000 known valid marine species living in the world's oceans and marine biota continue to be discovered and named steadily at a current average of 2,332 new species per year. The “average” newly described marine species is a benthic crustacean, annelid, or mollusc between 2 and 10 mm in size, living in the tropics at depths of 0–60 m, and represented in the description by 7–19 specimens. It is described after a shelf life of 13.5 years in an article with two to three authors in a journal with an IF <1, published by an academic institution or society or a small commercial publisher. It is highly likely that the description is not accompanied by molecular data and that its authors do not work in an institution in a region of the world where the new species comes from. At the current pace of discovery and characterization, it will take several hundred years to describe the remaining 1–2 million unknown marine species. With increased facilitation of access to literature, marine taxonomy will increasingly rely on retired professionals and citizen scientists. The barriers to new marine species descriptions are in part technological (access to habitats that are difficult to sample) and educational (training to generate and use molecular barcodes), but mostly institutional (funding of taxonomic work) and regulatory (restrictions imposed by access and benefit sharing legislation).